Comparative transcriptomics reveals eyestalk ablation induced responses of the neuroendocrine-immune system in the Pacific white shrimp Litopenaeus vannamei. Issue 106 (November 2020) - Liu, Jiahui; Zhou, Tingting; Wang, Chenggui; Wang, Wei; Chan, Siuming
Abstract: In decapod crustaceans, eyestalk ablation is widely used to expedite ovarian maturation and spawning because of the removal of a gonad inhibiting hormone produced by the X-organ sinus gland. However, eyestalk ablation also results in negative impacts on the immunocompetence of the eyestalk-ablated females. In the current study, we investigated the impact of eyestalk ablation on the transcriptomic responses of three major nervous organs of shrimp, including the eyestalk ganglion, brain and thoracic ganglion, using the Illumina Hiseq™ 4000 platform. A total of 48, 249 unigenes with an average length of 1253 bp and a N50 value of 2482 bp were obtained. Following eyestalk ablation treatment, a total of 2, 983, 6325 and 6575 unigenes were detected as differentially expressed (log2 Ratio >1 and FDR <0.05) from the eyestalk, brain and thoracic ganglia, respectively. Functional GO and KEGG analysis of these differential expression genes (DEGs) showed that these DEGs were associated with a wide variety of biological processes and pathways. The distribution of DEGs among three comparison groups was similar, and many DEGs were mapped to the phagosome pathway, indicating that eyestalk ablation triggers activation of the neuroendocrine-immune (NEI) system. Interestingly, several important pathways were uniquely enriched in the brain tissue, suggesting that the brain may play a crucial role in the NEI system in response to eyestalk ablation. This is the first report on the transcriptomic regulation of the nervous system in response to eyestalk ablation in L. vannamei . The genes and pathways identified in this study will help to elucidate the molecular mechanisms of neuroendocrine-immune responses to eyestalk ablation in penaeid shrimp. Highlights: Unilateral eyestalk ablation of shrimp triggered neuroendocrine-immune response of the nervous system. Brain was the major organ responding to eyestalk ablation. Pathways related to phagosome, neuroactive ligand-receptor interaction, and ECM-receptor interaction were activated.